2022
DOI: 10.3389/fnut.2022.871243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet light treatment on microbiological safety and quality of fresh produce: An overview

Abstract: Fresh and fresh-cut fruits and vegetables have been associated in several foodborne illness outbreaks. Although investigations from those outbreaks reported that the contamination with pathogenic microorganisms may occur at any point in the farm to fork continuum, effective control strategies are still being widely investigated. In that direction, the concept of hurdle technology involving a sequence of different interventions have been widely explored. Among those interventions, ultraviolet (UV) light alone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…By evaluating electrolyzed water in mushrooms, Ding et al [ 47 ] concluded that microbial growth inhibition reduced the production of organic acids, therefore, little variation in pH. Reduction of the microbial load is desired after UV-C application, which aims to reduce the number of microorganisms, control the onset of diseases, and hence product deterioration [ [48] , [49] , [50] , [51] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By evaluating electrolyzed water in mushrooms, Ding et al [ 47 ] concluded that microbial growth inhibition reduced the production of organic acids, therefore, little variation in pH. Reduction of the microbial load is desired after UV-C application, which aims to reduce the number of microorganisms, control the onset of diseases, and hence product deterioration [ [48] , [49] , [50] , [51] ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, radiation, especially UV-C, can suppress enzymatic browning due to its antibacterial properties, increasing total antioxidant capacity and reducing polyphenol-oxidase (PPO) activity [ 13 , 16 ]. UV-C is a non-toxic and non-invasive method with several advantages, which include the absence of chemical residues, zero waste generation, cost-effectiveness (low installation and maintenance costs), ease of implementation, environmental friendliness, low energy consumption, minimal impact on nutritional quality and organoleptic characteristics, and favorable consumer perception [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Cultivar-dependent responses in blueberry leaves were noted, whereby UV-B-resistant cultivars were seen to accumulate faster and reach higher levels of antioxidants as compared to sensitive cultivars [ 108 , 109 ]. Exposure of blueberries to UV-C has predominantly been used for fruit sterilization [ 110 ], although the application extends to increasing the antioxidant properties of the fruit [ 93 ].…”
Section: Light Interventions To Enhance Antioxidant Capacity In Fruitsmentioning
confidence: 99%
“…These multi-faceted approaches, known as hurdle technology, are commonly used to increase the efficacy of disinfectants [ 19 ]. Methods like ultraviolet radiation (UV), radio frequency (RF), ionizing radiation, and ultrasound are often utilized for disinfection; however, they are expensive and commonly prove impractical in small-scale operations [ 20 , 21 ]. In Japan, force aeration has been used along with water to wash surfaces or produce, destroying 90% more microorganisms [ 22 ].…”
Section: Introductionmentioning
confidence: 99%